2012
DOI: 10.1073/pnas.1117963109
|View full text |Cite|
|
Sign up to set email alerts
|

Protein disulfide isomerase homolog PDILT is required for quality control of sperm membrane protein ADAM3 and male fertility

Abstract: A disintegrin and metalloproteinase 3 (ADAM3) is a sperm membrane protein critical for both sperm migration from the uterus into the oviduct and sperm primary binding to the zona pellucida (ZP). Here we show that the testis-specific protein disulfide isomerase homolog (PDILT) cooperates with the testis-specific calreticulin-like chaperone, calsperin (CALR3), in the endoplasmic reticulum and plays an indispensable role in the disulfide-bond formation and folding of ADAM3. Pdilt −/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
167
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 133 publications
(179 citation statements)
references
References 56 publications
5
167
1
1
Order By: Relevance
“…1A). Cumulus cells support fertilization, and in vitro fertilization can be achieved more efficiently with them than without them (Jin et al, 2011;Tokuhiro et al, 2012). The molecular basis of this observation remains obscure; however, a few studies have addressed the function of cumulus cells (Oren-Benaroya et al, 2008;Shimada et al, 2008).…”
Section: The Nature Of Eggsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Cumulus cells support fertilization, and in vitro fertilization can be achieved more efficiently with them than without them (Jin et al, 2011;Tokuhiro et al, 2012). The molecular basis of this observation remains obscure; however, a few studies have addressed the function of cumulus cells (Oren-Benaroya et al, 2008;Shimada et al, 2008).…”
Section: The Nature Of Eggsmentioning
confidence: 99%
“…Mice deficient for the testis-specific molecular chaperone PDILT produce spermatozoa that, based on in vitro experiments, exhibit impaired zona-binding ability (Tokuhiro et al, 2012). After crossing with a transgenic fluorescently tagged sperm line (Hasuwa et al, 2010), the failure of sperm migration into the oviduct was indicated by live imaging.…”
Section: The Zona-binding Ability Of Spermatozoamentioning
confidence: 99%
“…as listed in Table 3, Pdilt-disrupted mice produce spermatozoa with impaired zona binding ability [53]. We crossed this mouse line with another transgenic mouse line with fluorescent proteintagged sperm [20] for visibility in the female reproductive tract.…”
Section: The "Zona-binding Ability" Of Spermatozoa Must Be Reconsideredmentioning
confidence: 99%
“…The DNA fragments were inserted to the pNT1.1 vector. 47 The resulting donor plasmid, termed pNT1.1-SUN1, harbors the neomycin resistant gene cassette in between the genomic DNA fragments. HeLa cells co-transfected with px330-SUN1 and pNT1.1-SUN1 were selected for G418-resistance.…”
Section: Establishment Of a Sun1 Knockout Cell Linementioning
confidence: 99%